Doubt : a history : the great doubters and their legacy of innovation, from Socrates and Jesus to Thomas Jefferson and Emily Dickinson - Hecht, Jennifer Michael, 1965- (New York, NY : HarperSanFrancisco, 2004)
In this sweeping history, Jennifer Michael Hecht celebrates doubt as an engine of creativity and as an alternative to the political and intellectual dangers of certainty -- Just as belief has its own history featuring people whose unique expressions of faith have forever changed the world, doubt has a vibrant story and tradition with its own saints martyrs, and sages.
Doubt is no shadow: a quiz and a guide to the question -- Whatever happened to Zeus and Hera?, 600 BCE-1 CE: Greek doubt -- Smacking the temple, 600 BCE-1 CE: doubt and the ancient Jews -- What the Buddha saw, 600 BCE-1 CE: ancient doubt in Asia -- When in Rome in doubt, 50 BCE-1 CE: empire in reason -- Christian doubt, Zen, Elisha, and Hypatia, 1-800 CE: late-classical mix -- Medieval doubt loops-the-loop, 800-1400: Muslims to Jews to Christians -- Printing press and the Age of Martyrs, 1400-1600: Renaissance and inquisition -- Sunspots and White House doubters, 1600-1800: revolutions in the authority of reason -- Doubt's bid for a better work, 1800-1900: freethinking in the age of science and reform -- Principles of uncertainty, 1900-: the new cosmopolitan -- Joy of doubt: ethics, logic, mood.
Includes bibliographical references (p. [521]-528) and index.
Keywords: Belief and doubt -- History